2021
DOI: 10.1002/pen.25718
|View full text |Cite
|
Sign up to set email alerts
|

The structural language of crystalline polymers*

Abstract: In sharp contrast with their amorphous counterparts, crystalline polymers provide a wealth of information on their chain conformation, the packing of the chains in unit‐cells, the existence or not of mirror symmetric conformations, on the crystalline lamellae, on the folds linking the crystalline stems, and so forth. Three illustrations of these insights are presented here: (a) the orientation of polymer folds in crystalline lamellae, (b) the complete structural analysis of the alpha phase of isotactic polypro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…This 40-fold slowing down of growth rate in the blends of copolymers compared to pure SC and the constant spherulitic growth rate with time suggest that the selection of crystallizable units from the copolymers happens at the growth front. Second, some previous results evidenced that selection of helical chains with the right chirality happened at the lamellar growth front rather than far away from the crystal surface. Lotz et al observed the width of microtwinning in single crystals of poly­(vinylcyclohexane), and the inheritance of the crystal lattice structure demonstrated unambiguously that the selection of chain conformation for crystallization happened at the crystal growth front. Third, from the same rate of enthalpy relaxation in the glassy state but different nucleation rates of melt crystallization of the PLLA homopolymer and the random copolymers, Androsch and Schick , demonstrated that the segregation of defect in PLLA random copolymers did not happen in the equilibrium melt but during crystallization.…”
Section: Discussionmentioning
confidence: 99%
“…This 40-fold slowing down of growth rate in the blends of copolymers compared to pure SC and the constant spherulitic growth rate with time suggest that the selection of crystallizable units from the copolymers happens at the growth front. Second, some previous results evidenced that selection of helical chains with the right chirality happened at the lamellar growth front rather than far away from the crystal surface. Lotz et al observed the width of microtwinning in single crystals of poly­(vinylcyclohexane), and the inheritance of the crystal lattice structure demonstrated unambiguously that the selection of chain conformation for crystallization happened at the crystal growth front. Third, from the same rate of enthalpy relaxation in the glassy state but different nucleation rates of melt crystallization of the PLLA homopolymer and the random copolymers, Androsch and Schick , demonstrated that the segregation of defect in PLLA random copolymers did not happen in the equilibrium melt but during crystallization.…”
Section: Discussionmentioning
confidence: 99%
“…Other articles in this volume, although not being explicitly fundamental studies, include very fundamental and general concepts as the mathematically elegant description of weak gels formed by cartilage components by fractional calculus in the article by Ferenc Horkay and Jack Douglas [ 5 ] or the application of the Ozawa‐Avrami model for the crystallization kinetics of materials for additive manufacturing by Alexis Thézé et al [ 6 ] Finally, Bernard Lotz [ 7 ] makes a strong point for the fundamental relevance of crystalline polymers, a sometimes‐neglected topic in polymer physics.…”
Section: Figurementioning
confidence: 99%
“…The question of unifying ion conductivity and stability in membranes and how to solve it by an aligned microstructure is tackled by Pitia et al [ 8 ] Methods to produce microfibers for battery application by means of polymer precursors are presented by Gabriel Gonzalez et al [ 9 ] Polymers with high intrinsic microporosity for gas‐separation membranes are studied by a combination of dynamical methods by Kolmangadi et al [ 10 ] Yucheng Wang et al [ 11 ] use a similar technique as used in ref. [7] for surface decoration here as a preparative tool to obtain highly oriented crystalline polymer layers. Materials of less technological but more cross‐disciplinary relevance, namely ambers, are studied by Kong et al [ 12 ] with respect to their polymeric network structure.…”
Section: Figurementioning
confidence: 99%